Prediction of financial condition of Indonesian banks using Altman Z-Score model - St Ibrah Mustafa Kamal; Luksi Visita (Journal of Islamic Economics, Management, and Business (JIEMB), 2020)
Purpose – Banking is one of the hearts of the economy in Indonesia. This study aims to determine the financial condition of banking in Indonesia.Method – The data in this study uses financial reports of bank. The technique of data analysis uses the Altman Z-Score model. By using five variables that represent the liquidity ratio X1, X2 and X3 profitability, X4 and X5 activities. With the criteria of assessment Z-Score 2.99, it is categorized as a very healthy company. 1.81 Z-Score 2.99 is in the gray area so that the probability of being saved and the possibility of bankruptcy is the same depending on the policy decision of the company management as the decision maker. Z-Score 1.81 is categorized as a company which has an enormous financial problem at high risk, so that the possibility of bankruptcy is very largeResult – As the result, it can be seen that Indonesian banks from 2008-2010 were at risk of going through financial difficulties and then survived and in the following years became more stable, while some banks were in unstable but survived and fixed their financial issues.Implication – This research can help Indonesian banks to evaluate their financial performanceOriginality – The originality of this research lies in the object under study, test analysis, and research location.